TP10.1.12Personal Protective Equipment impairs pulmonary gas exchange causing systemic hypercapnia-hypoxaemia and cerebral hyperperfusion-induced cephalalgia. (28th October 2021) - James, Osian; Stacey, Benjamin; Hopkins, Luke; Robinson, David; Bailey, Damian; Lewis, Wyn
Abstract: Aims: To what extent Personal Protective Equipment (PPE) impacts integrated cardiopulmonary-cerebrovascular function has not been examined. The hypothesis tested was that PPE adversely influences pulmonary gas exchange, resulting in systemic hypercapnic-hypoxaemia and cerebral hyperperfusion-induced cephalalgia. Methods: Eight male Higher Surgical Trainees (aged 33 ± 2y) participated in a repeated measures crossover study, completing two-hour laparoscopic simulation tasks, on two separate occasions (separate days), once in standard operating attire, and once in full PPE (including FFP3 mask). Results: Following two hours of simulation, full PPE (compared with standard operating attire) was associated with increased FI CO2 (7.9% (±0.8%) vs. 7.1% (±1.2%); p = 0.025), decreased FI O2 (16.0% (±0.4%) vs. 16.6% (±0.5%); p = 0.011), and decreased peripheral O2 saturation (95% (± 1%) vs. 98% (±1%); p = 0.001). Headaches were reported by three participants in PPE (Chi 2 3.692, p = 0.055), and was associated with increased Middle Cerebral Artery flow velocity; 82 (±4) cm/s, compared with 63 (±9) cm/s in the remaining five participants (p = 0.008). Skin temperature increased by 1.3 °C during simulation in PPE (p = 0.001), with an equal mean insensible fluid loss of 300ml under both conditions (p = 0.049). Conclusions: Collectively, these findings highlight the integrated cardiopulmonary-cerebrovascular complications associated with PPE-induced impairment in pulmonary gas exchange. Protective countermeasures should be designed to prevent risk to healthcare staff and patients alike.